2015
DOI: 10.1016/j.ijbiomac.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte complex containing silver nanoparticles with antitumor property on Caco-2 colon cancer cells

Abstract: Polyelectrolyte complex (beads) based on N,N,N-trimethyl chitosan/alginate was successful obtained and silver nanoparticles (AgNPs) were loaded within beads. In vitro cytotoxicity assays using beads/silver nanoparticles (beads/AgNPs) provided results, indicating that this material significantly inhibited the growth of colon cancer cells (Caco-2). In vitro release studies showed that the beads stabilized AgNPs and repressed Ag(0) oxidation under gastric conditions (pH 2.0). On the other hand, at physiological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Several methodologies for TMC synthesis are described in the literature. [34][35][36] Cs reduction can be easily mediated by iodomethane in sodium iodide presence and strong alkaline condition, using N-methyl-2-pyrrolidone (NMP) as solvent. 37,38 Some authors reported the use of dimethylsulfate like reduction agent instead iodomethane, because it has higher stability and it can be used as solvent in the reaction for TMC production as well.…”
Section: Methodologies To Convert Chitinderivatives Into Hydrogelmentioning
confidence: 99%
“…Several methodologies for TMC synthesis are described in the literature. [34][35][36] Cs reduction can be easily mediated by iodomethane in sodium iodide presence and strong alkaline condition, using N-methyl-2-pyrrolidone (NMP) as solvent. 37,38 Some authors reported the use of dimethylsulfate like reduction agent instead iodomethane, because it has higher stability and it can be used as solvent in the reaction for TMC production as well.…”
Section: Methodologies To Convert Chitinderivatives Into Hydrogelmentioning
confidence: 99%
“…The cationic property of TMC allows its association with polyanionic macromolecules, like heparin, sodium alginate, among others [20,21]. TMC/heparin multilayer thin films carried out from the layer-by-layer assembly [20,22].…”
Section: Most Recent Tmc Applicationsmentioning
confidence: 99%
“…This previous study suggested that the antibacterial activity of the beads loaded with AgNPs of 3.3 mg/ml might be from the silver ion (Ag + ) released into the system [6]. Furthermore, another study reported that no Ag + was released from N,N,N-trimethyl chitosan/alginate/AgNP beads in buffer, pH 2 but this release could be observed in buffer, pH 7.4 [9]. This might be because of electric repulsions between hydronium ion (H 3 O + ) and the positive charge of chitosan/alginate beads, which could inhibit the swelling of the beads and the release of Ag + in buffer, pH 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, another study reported that no Ag + was released from N,N,N-trimethyl chitosan/alginate/AgNP beads in buffer, pH 2 but this release could be observed in buffer, pH 7.4 [9]. This might be because of electric repulsions between hydronium ion (H 3 O + ) and the positive charge of chitosan/alginate beads, which could inhibit the swelling of the beads and the release of Ag + in buffer, pH 2 [9]. Moreover, the carboxylic group (-COOH) of alginate are not ionized at pH 2, which will also decrease the release of Ag + from the beads [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation